Zubay's principles of biochemistry - Veer Bala Rastogi (Medtech, 2017)
Principles of biochemistry has been prepared by three distinguished authors of Chemistry/Biochemisty known for their academic excellence and pedagogical approach in teaching the subject at graduate and post graduate level.